Carnegie International 1991 : Volume I - Volume II - Cooke, Lynne; Francis, Mark; Carnegie International 1991, Pittsburgh (Pittsburgh : The Carnegie Musuem of Art, 1991)
Asher, Michael ; Avedon, Richard ; Barry, Judith ; Baumgarten, Lothar ; Boltanski, Christian ; Bourgeois, Louise ; Cage, John ; Calle, Sophie ; Coleman, James ; Cragg, Tony ; Deacon, Richard ; Dujourie, Lili ; Fritsch, Katharina ; Frize, Bernard ; Graham, Dan ; Hamilton, Richard ; Hammons, David ; Huang Yong Ping ; Jarman, Derek ; Kabakov, Ilya ; Kawara, On ; Kelley, Mike ; Lawler, Louise ; Lum, Ken ; McCollum, Allan ; McCracken, John ; Michailov, Boris ; Milroy, Lisa ; Miyajima, Tatsuo ; Mucha, Reinhard ; Muñoz, Juan ; Nauman, Bruce ; Nordman, Maria ; Paolini, Giulio ; Prina, Stephen ; Rollins + K.O.S., Tim ; Serra, Richard ; Struth, Thomas ; Sugimoto, Hiroshi ; Taaffe, Philip ; Williams, Christopher ; Wool, Christopher
2 delen: volume I en volume II
Carnegie International 1991, The Carnegie Musuem of Art, Pittsburgh, October 19, 1991 - February 16, 1992
boek